Second Track Citizens' Diplomacy: Concepts and Techniques for Conflict Transformation - Davies, John L.; Kaufman, Edward (Edy) (Rowman & Littlefield Publishers, 2003)
Almost all current wars are primarily intra-state, involving complex societal conflicts with at least one party a non-state community. Second Track/ Citizens' Diplomacy is broadly defined as facilitated dialogue to address conflict issues between unofficial representatives or equivalent opinion leaders dfrom communities in conflict. It is an essential complement to official (first track) diplomacy for responding to the enormous challenge that these complex conflicts pose to building a sustainable and dynamic peace. In this volume, prominent contributors explain the development, theory and current practice of second track diplomacy. They examine the dynamics of modern complex conflicts, such as those in Sri Lanka, Israel/Palestine, Cyprus, or the Caucasus. Exploring innovative problem-solving methodologies, the book provides a detailed program for guiding 'Partners in Conflict' in the search for common ground and analyzes core issues that arise in the practice and evaluation of second track diplomacy. This book will be valuable to both academics and professionals involved in first or second track diplomacy, or interested in integrative methods of dispute resolution or conflict prevention, as well as to those working in development, peace-building or humanitarian programs at any phase of the conflict cycle.